2015
DOI: 10.2174/2210289201506010024
|View full text |Cite
|
Sign up to set email alerts
|

Metals Contents in Spices and Herbs Available on the Egyptian Market: Assessment of Potential Human Health Risk

Abstract: Spices and herbs are being used as a diet ingredient often to improve color, aroma and acceptability of food. The contamination of spices with heavy metals may result in the accumulation of these metals in the body organs. The aim of the present study was to investigate As, Cu, Fe and Zn contents in the most popular spices and herbs that are used in Egyptian cuisine. Ten samples were purchased directly from the local markets in Egypt. Arsenic, Copper, Iron and Zinc contents in the samples were determined by at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Extremely high TTHQ values of Cr have been found in Green Chili, ginger, coriander leaf, and all forms of chili powder and turmeric powder. Our research had a higher TTHQ score than previous studies conducted in Poland, Pakistan, Egypt, and Nigeria (9, 22, 46, 47).…”
Section: Resultscontrasting
confidence: 71%
“…Extremely high TTHQ values of Cr have been found in Green Chili, ginger, coriander leaf, and all forms of chili powder and turmeric powder. Our research had a higher TTHQ score than previous studies conducted in Poland, Pakistan, Egypt, and Nigeria (9, 22, 46, 47).…”
Section: Resultscontrasting
confidence: 71%
“…Similarly low values of THQ were obtained by authors of other studies. In Egypt, in a study on spices, the values for As were up to 7.50 × 10 −2 [ 70 ]; in a study conducted in Ethiopia, the values obtained for Pb were up to 30.75 × 10 −2 [ 71 ]; in a study on herbal products, conducted in Ghana, the following values of THQ were obtained: in the case of As—up to 8.28 × 10 −2 , for Cd—up to 0.0015, for Pb—up to 0.0034, and for Hg—up to 0.0001 [ 72 ]. In another study conducted in Ghana, the values of THQ in the case of absorption of heavy metals related with the consumption of tea were as follows: for As—up to 0.89, for Pb—up to 0.0109, and for Cd—up to 2.00 × 10 −1 [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The author observed that spice grinding in commercial mills can lead to the incorporation of 3 to 5 times more Fe, due to the wear of the grinding equipment used in this process. High levels of Fe have also been reported by De La Calle et al 20 (1264 ± 216 mg kg -1 ), Jawad 21 (481.28 ± 2.37 mg kg -1 ), Karadaş et al 19 (158 ± 19 mg kg -1 ), Matloob 8 (194.1 ± 39.03 mg kg -1 ), Özcan et al 17 (89.24 ± 11.43 mg kg -1 ), Seddigi et al 7 (144 ± 9.2 mg kg -1 ), Singh and Garg 14 (76.0 mg kg -1 ), Soliman 25 (620.02 ± 541.36 mg kg -1 ) and Soylak et al 12 (281.8 ± 20.5 mg kg -1 ).…”
Section: Discussionmentioning
confidence: 95%